PENGEMBANGAN KIT PRAKTIKUM KIMIA BERWAWASAN LINGKUNGAN - I Ketut Lasia; Ni Made Wiratini (UIN Sunan Kalijaga Yogyakarta, 2016)
The purpose of this research to develop environmentally chemistry lab kits to support laboratory of environmental friendly chemistry (green chemistry laboratory). The development refers to the model of Education Research and Development. The product was a chemistry lab KIT containing environmentally friendly lab materials, tools, and practical procedure that can be carried in the classroom. Results validisi expert on chemistry lab procedures showed very valid in either category. The response of students to 95.6% expressed a good product.